An objective comparison of speech intelligibility and quality of hearing aid of different companies. - Gowthami, Basappanapalya; Nisha, Kavassery; Uppunda, Ajith (Journal of the All India Institute of Speech & Hearing)
Purpose: This study aimed to verify the intelligibility and quality of hearing aid-processed speech across companies through objective measures. The output of hearing aids programmed to different prescriptive formulae (Company fit, NAL NL 1, NAL NL 2, and DSLv5) across companies (Company I, Company II, Company III, Company IV, and Company V) were recorded and stored in the sound level meter connected to the manikin. Materials and Methods: Offline analysis of speech quality of the recorded speech was done using the Hearing Aid Speech Quality Index (HASQI), the intelligibilty was measured using the Hearing Aid Speech Perception Index (HASPI) and Speech Intelligibility Index (SII), and Long-Term Average Speech Spectrum (LTASS) was used to measure the spectral composition of speech. Results: When the companies are compared, the hearing aid of Company V showed significantly higher SII values for all prescriptive formulae indicative of better speech intelligibility provided by Company V hearing aids. In terms of speech quality, all the hearing aids showed similar HASQI values. Conclusions: The reasons for each of these findings are highlighted and recommendations for best practices on the use of objective measures for verifying the hearing aid output in clinical setups are suggested.